Teacher Professionalism Development in TVET System: Preparedness, In-Service Trainings and Challenges - Philogene, Manirahari; Zhiyuan, Sun; Nyoni, Precious (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This study aims to analyze the professionalism of Technical and Vocational Education and Training (TVET) teachers in Rwanda and provide evidence-based recommendations for improvement. Methodology: Utilizing qualitative methods, this study employed document analysis and semi-structured interviews to gather data. The analysis was conducted using UNESCO’s Global Framework of Professional Teaching Standards, offering a comprehensive examination of TVET teachers’ professionalism through detailed reviews and insightful interviews. Main Findings: The study revealed that only 31.1% of TVET teachers received adequate training during the 2021/22 academic year. This disparity is attributed to delayed deployment, inefficiencies in human resource development, a shortage of private higher learning institutions, static salary payment systems, and limited collaboration. Novelty/Originality of this study: This research stands out due to its thorough assessment of the professionalism of Rwandan TVET teachers in line with the Global Framework. It highlights existing challenges and proposes evidence-based solutions to enhance their preparation, in-service training, and effectiveness in today’s dynamic educational environment.